Simulated Individualized Education Program Meetings: Valuable Pedagogy Within a Preservice Special Educator Program. (August 2019) - Mueller, Tracy Gershwin; Massafra, Aimee; Robinson, Jason; Peterson, Lori
Research about Individualized Education Program (IEP) meeting outcomes indicates special educators are unprepared and uncertain about practices designed to encourage meaningful IEP team participation. In response to these challenges, we crafted a simulated IEP (SIEP) project for preservice special education teachers as part of their licensure program. Using research-based simulation guidelines, preservice special education teachers were required to prepare, participate, and debrief with IEP team member volunteers and professors about the process. To evaluate the social validity of the SIEP project, we conducted qualitative interviews with 60 graduates of the program. Findings revealed five major themes that highlight value in the experience, including (a) valuable preparation for the future, (b) practical application of educational theory, (c) a safe space to learn and make mistakes, (d) real-world practice collaborating as a team, and (e) an opportunity to gain meaningful feedback. Following the presentation of themes, we discuss implications for practice and future research.